Opportunities to Use Innovative Approaches and Methods in Teaching Foreign Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article reflects on the use of modern innovative technologies in the teaching of foreign languages and their effectiveness. Also, increasing interest in the foreign language that students are learning to exploit the internal capabilities of their memory, to their own power in students includes generating confidence.